USING QUALITY OF SERVICE VIRTUAL PRIVATE NETWORK (VPN) ON E-KTP BANDAR LAMPUNG - Novi Herawadi Sudibyo; Muhammad Said Hasibuan (Proceeding International Conference on Information Technology and Business, 2015)
Implementation e-ktp in Bandar Lampung , there areseveral obstaclesin the field, among others, areoftendelays inthe exchange of databetween theserverthatislocatedin the districtandthat is inthe centralserver. Tofindthe cause ofthese obstaclesand the importance ofthequality ofnetwork servicesit is necessarytodothemeasurementthatcanbeusedtomeasurethePerformance of/qualityofnetworkservice VPN that isused in theimplementation of E-Ktpin Bandar Lampungon each -eachin the district, the main problemin this studyis